Answer:
The required form of the given expression is : (a + 4)(b + 1)
Step-by-step explanation:
The given expression is : ab + 4 + a + 4b
We need to factor he given expression and arrange the factors in the alphabetic order.
To find the factors of the given expression, we need to use the concept of algebra :
ab + 4 + a+ 4b
First rearranging the terms in order to form the factors :
= ab + 4b + 4 + a
= b(a + 4) + 1(4 + a)
= b(a + 4) + 1(a + 4)
= (b + 1)(a + 4)
Now, the factors in the alphabetic order :
= (a + 4)(b + 1)
Hence, the required form of the given expression is : (a + 4)(b + 1)